Risk Factors of Recurrent Diabetic Ketoacidosis in Karbala Teaching Hospital for Children - Ahmed Kareem Mohammed; Zena Kareem Mohammed (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Diabetic ketoacidosis (DKA) is defined as life threatening condition that happen mainly in T1DM and less frequently with T2DM in certain situation, an increase in the serum concentration of ketones greater than 3 mmol/L, a blood sugar level greater than 11mmol/L (although it is usually much higher), and a blood (usually arterial) pH less than 7.3 and it is the most frequent acute hyperglycemic emergency in persons with diabetes mellitus (DM). The main cause of morbidity and mortality in children with diabetes is DKA from both type1 DM (T1DM) and T2DM. Children with diminished metabolic control or previous episodes of DKA are at higher risk, as are prepubescent and adolescent girls, children with psychiatric disorders, such as eating disorders, and children who come from challenging families with lower socioeconomic status and inadequate health insurance as well as low general education levels.